Multiresponsive Transitions of PDMAEMA Brushes for Tunable Surface Patterning - Flemming, Patricia; Janke, Andreas; Simon, Frank; Fery, Andreas; Muench, Alexander S.; Uhlmann, Petra (Langmuir, 2020)
Poly(N,N-dimethylaminoethyl methacrylate) (PDMAEMA) is an attractive polymer for switchable surface coatings based on its multiresponsiveness toward environmental triggers (temperature, pH-value, ionic strength). In this in situ study, we present the complex and tunable thermoresponsiveness of PDMAEMA Guiselin brushes (9 nm, dry thickness), which were prepared via an efficient grafting-to approach. Combining in situ atomic force microscopy (AFM) visualizing the surface topography (x-y plane) and spectroscopic ellipsometry monitoring the swelling behavior of the polymer film (layer thickness, z-direction) offers for the first time a three-dimensional insight into thermoresponsive transitions on the nanoscale. While PDMAEMA films exhibit LCST behavior in the presence of monovalent counterions, it can easily be switched toward an UCST thermoresponsiveness via the addition of small quantities of multivalent ions. In both cases, the transition temperature as well as the sharpness and reversibility of the transition can be tuned via a second external trigger, the ionic strength. Whereas homogeneous surfaces were observed both below and above the LCST in monovalent salt solutions, the UCST transition was characterized by the in situ formation of a nanostructured surface of pinned PDMAEMA micelles with entrapped multivalent counterions. Moreover, it was demonstrated for the first time that the characteristic dimensions of the nanopattern (the diameter and height of the pinned micelles) could be tuned in situ by the pH- A nd induced UCST thermoresponsiveness of PDMAEMA. This approach therefore provides a novel bottom-up strategy to create and control polymeric nanostructures in an aqueous environment.
CRIS-Team Scopus Importer:2022-04-14